Teknologi Informasi dan Komunikasi (TIK) dalam Pembelajaran di Sekolah Dasar (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Learning in the 21st century must be ICT-based. Professional elementary school teachers in the 21st century are teachers who can facilitate student learning. PGSD Study Program, STKIP Kusuma Negara through MK KKL held a national webinar with the theme Creative and Innovative Elementary School Teachers through ICT Implementation. This webinar was held online via the zoom meeting application and was attended by 287 participants, consisting of elementary school teachers, educational practitioners, and students (STKIP Kusuma Negara and the general public). The aim of this training is to equip elementary school teachers to be creative and innovative through the implementation of ICT. The stages of implementing the national webinar go through three stages, namely planning, implementation and evaluation. The national webinar material is Creative and Innovative Teachers Through Digital-Based Implementation and Innovative I-Teaching Teaching and Digital Tools. Schools are places to facilitate teachers in implementing ICT in the learning process to make learning creative and innovative. However, in reality in the field only students are able to use ICT tools. So that ICT-based learning does not become two-way. As a result, teachers are increasingly distant from ICT. Teachers must be able to implement ICT to create e-teaching and e-learning based learning.